EXTERNALIDADES DE UM SISTEMA DE PRODUÇÃO AGRÍCOLA E PECUÁRIO - Eurich, Joelcio (2016)
Agriculture and generally livestock, the way in which they were driven from the green revolution walked deep-rooted form of externalities are these positive and / or negative,and in this context there is a need for improvement of applicable methodologies to map these, so this study aims to assess the dynamics of a unit of agricultural and livestock production temporally through emergy methodologies and inventory of greenhouse gases - GHGs. For the evaluation of proposed methodologies used a unit of agricultural and livestock production in the municipality of Carambei, state of Paraná, Brazil, and this computed data eleven years, starting in 2005 and ending in the year 2016 range this that makes up ten years of mainly agricultural production and a year with the entry of the livestock sector, this important dynamic in the time proposed comparison. By Emergy methodology sought to calculate besides the Transformity values (Tr), Renewability (%R), Income Ratio Emergy Net (EYR), Emergy Investment Ratio (EIR), Environmental load (ELR) and Sustainability Index (SI) and through the GHG inventory evaluation established that the calculations for the application of organic fertilizers, synthetic nitrogenous fertilizers, lime, urea, pesticides, also enteric fermentation, handling of animal waste (nitrous oxide and methane) , secondary sources of N2O (atmospheric deposition and leaching or runoff), crop residues, mechanized operations, electric power and combustion stationary. As the emergy methodology there was a major change of Tr values over the period studied reaching extreme values of 60276.40 sej.J-1 in year three to 121,255.08 sej.J-1 in the last year of study in However other values observed for% R,EYR, EIR, ELR and SI have not undergone substantial change, and generally behaved as regular, as the GHG observed an important dynamic of CO2 mitigation on the ground,starting from value of 13.76 t ha-1 at baseline to 39.15 Mg ha-1 in the last year survey, with special contribution of the livestock sector in this dynamic, as GHG emissions was observed that the entrance of livestock sector in the unit contributed decisively to a significant increase, especially influenced by the CH4 emission arising from enteric fermentation, however when computing the balance of CO2eq for the period studied there was no major change presenting minimum value of 4.93 MgCO2eq ha-1 in year four and a value of 6.75 MgCO2eq ha-1 in the last year of study, through the relationship established between the two methods was found to be an important change of the unit studied from the entrance to the livestock sector, the ratio Tr / CO2 balance showed minimum values 8.18 in the year seven to maximum 16.55 in the past year and the produced energy ratio (MJ) for the issuance of CO2eq (kg) showed 30.62 MJ values KgCO2eq-1 in year 2 to 8.97 MJ KgCO2eq-1 in the last year. In general it can be concluded that there was a negative change in the order of 65% for the system as a whole is subject to the emergy aspects and greenhouse gases listed after the entry of the livestock sector in the studied unit.